The end of the era of the big newspaper publishers and the emergence of the new digital models. The restructuring of the business of information in Spain in the first two decades of the 21st century - Sánchez Illán, Juan Carlos; Luena Lopez, César (Universidad Pedagógica y Tecnológica de Colombia, 2021)
During the 20th century, the prevalence of well-known publishers, with substantial political and business profiles, such as Nicolás María de Urgoiti, Luis Montiel Balanzat, and Ángel Herrera Oria, as the authentic journalistic dynasties, presided over the editorial and ideological landscape of the Spanish press in a relatively clear way. The death, in 2007, of what can be considered the last of the great classical publishers, Jesús de Polanco, marked, to a large degree, the end of an era in Spanish publishing, recognized globally as that of the great magnates of journalistic communication. In the two first decades of the 21st century, the emergence of new patrons of the press has been witnessed, oriented towards the editing of media which came into being in the digital environment. In this work, this change of the editorial paradigm is explored through interviews and with methods of analysis that are essentially qualitative. For this, the underlying philosophy will be the proposal of Ortega of the vital analysis of the trajectory of the protagonists and their journalistic media within the historical circumstances, as a fundamental explanatory element.